Teachers and peer teacher students’ perceptions on ICT tools usage in peer learning projects: findings from a multiple case study - Carvalho, Ana Raquel (2021)
Preparing learners for the demands of 21st century society requires a comprehensive approach that integrates the development of cognitive and interpersonal skills as well as the choice for innovative pedagogical strategies that assign teachers and learners new roles and give room for the integration of technology enhanced learning. Peer learning promotes collaboration and interaction between peers and can be used by teachers as a powerful strategy to foster students’ cognitive, affective and social skills. The inclusion of ICT tools in peer learning programs has become more and more relevant based on their potential to foster learners’ autonomy, collaboration, and communication skills as well as on the pervasiveness of mobile and social media tools. The present multiple case study focuses on analyzing the role of ICT tools in five peer learning projects implemented in five Portuguese educational institutions through the perceptions of teachers and peer teacher students who integrated them. A semi-structured interview and a survey by questionnaire were the tools used and the data collected were treated under content analysis and descriptive statistics. Findings from this study are expected to add insight into the state of the art of ICT tools usage and role in promoting effective learning in peer learning projects.